GENERAL PECULIARITIES OF COMPOSITE SENTENCES IN ENGLISH AND UZBEK (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the general peculiarities of composite sentences in English and Uzbek from a comparative and typological perspective. Composite sentences are analyzed as syntactic structures consisting of two or more clauses connected through coordination or subordination. The study highlights the structural types of composite sentences in both languages, including compound and complex sentences, and explores the grammatical means used to establish clause relations. Special attention is paid to differences in word order, syntactic organization, and typological features, such as the analytic nature of English and the agglutinative character of Uzbek. The findings of the article contribute to a deeper understanding of cross-linguistic similarities and differences in sentence structure and are relevant for contrastive linguistics, translation studies, and language teaching..